Emerging information resources management and technologies - Khosrow-Pour, Mehdi (Idea Group Publishing, 2007)
In the time of constant technological and managerial advancement, firms of the 21st century are faced with an ongoing quest for implementing more effective strategies and methodologies to remain at the apex of the information resources management industry. Researchers and pioneers of academia incessantly delve into potential solutions to increase efficacy within technological and information resources management, as well as identify the emerging technologies and trends. Emerging Information Resources Management and Technologies supplies the industry leaders, practicing managers, researchers, experts, and educators with the most current findings on undertaking the operation of the latest information technology reforms, developments, and changes. Emerging Information Resources Management and Technologies presents the issues facing modern organizations and provides the most recent strategies in overcoming the obstacles of the ever-evolving information management and utilization industry